Behavioral Genetics of the Mouse : Genetics of Behavioral Phenotypes. - Crusio, Wim E. (Cambridge handbooks in behavioural genetics., 2013)
A comprehensive review of the current state of our knowledge on the inheritance of normal behaviour in the laboratory mouse.